Activating CoMoS with CoP3 Phase for High‐efficient Hydrogen Evolution Reaction in Acidic Condition. Issue 5 (15th January 2021) - Du, Yunmei; Wang, Wensi; Zhao, Huimin; Jiang, Xianliang; Liu, Yanru; Chen, Ruixin; Yang, Bo; Wang, Lei
Abstract: Currently, the construction of heterostructures to optimize electrocatalytic activities is a hot research topic, since there is still a certain gap between the electrocatalytic properties of these heterostructures and that of Pt/C. With this in mind, we utilized in‐situ vapor‐phase phosphorization‐sulfurization to obtain the CoP3 /MoS2 −Co0.75 Mo3 S3.75 (CoP/CoMoS, for short) heterostructure on carbon cloth (CC), which exhibits Pt‐like electrocatalytic performance and excellent stability in acid electrolyte. Activated by CoP3 active phase, the electronic configuration of CoMoS and the adsorption energy of H* (▵GH* ) are greatly optimized. Meanwhile, the rapid oxidation of CoMoS phase can be effectively avoided under the protection of CoP3 layer. This work provides a reference for the design of heterostructures and their mechanism of action in electrocatalysis. Abstract : Working together : The CoP/CoMoS heterostructure and the carbon substrate have a stable overall structure. Notably, the existence of CoP3 phase increases HER active sites and promotes the optimization of the electronic structure of the CoMoS phase, thus accelerating the HER process. Moreover, the catalytic activity of the CoMoS interlayer is maintained under the protection of the CoP3 outmost layer, conferring long‐term electrochemical durability.